Transgene sequences free of CG dinucleotides lead to high level, long-term expression in the lung independent of plasmid backbone design - Bazzani, R; Pringle, I; Connolly, M; Davies, L; Sumner-Jones, S; Schleef, M; Hyde, S; Gill, D (Elsevier, 2016)
Non-viral aerosol gene therapy offers great potential for treating chronic lung diseases of the airways such as cystic fibrosis (CF). Early clinical trials showed that transgene expression in the airways was transient whereas maximal duration of transgene expression is essential in order to minimise the frequency of aerosol treatments. Improved vector design, such as careful selection of the promoter/enhancer, can lead to more persistent levels of transgene expression, but multiple factors affect expression in vivo. Following aerosol delivery to the lungs of mice, we measured reporter gene expression from a CpG-free luciferase transgene cassette in the context of both a plasmid and minicircle vector configuration and showed that the vector backbone had no effect on expression. Transgene activity was affected by the vector backbone however, when a similar, but sub-optimal CpG-containing transgene was used, suggesting that aspects of the plasmid backbone had a negative impact on transgene expression. Similar studies were performed in Toll-like receptor-9 (TLR9) knockout mice to investigate a potential role for the TLR9 signalling pathway in detecting CpGs in the vector sequence. Even in the absence of TLR9, persistent expression could only be achieved with a CpG-free transgene. Together, these data indicate that in order to achieve high levels of persistent expression in vivo, a CpG-free transgene cassette is required.